HDR Brachytherapy in the Management of High-Risk Prostate Cancer - Susan Masson; Raj Persad; Amit Bahl (Advances in Urology)
High-dose-rate (HDR) brachytherapy is used with increasing frequency for the treatment of prostate cancer. It is a technique which allows delivery of large individual fractions to the prostate without exposing adjacent normal tissues to unacceptable toxicity. This approach is particularly favourable in prostate cancer where tumours are highly sensitive to dose escalation and to increases in radiotherapy fraction size, due to the unique radiobiological behaviour of prostate cancers in contrast with other malignancies. In this paper we discuss the rationale and the increasing body of clinical evidence for the use of this technique in patients with high-risk prostate cancer, where it is combined with external beam radiotherapy. We highlight practical aspects of delivering treatment and discuss toxicity and limitations, with particular reference to current practice in the United Kingdom.